Tunable Elliptical Split Ring Resonator Using Single Varactor Diode - Elkorany, A. S.; Ahmed, G.; Saleeb, D.; Mohamed, H. A. (Advanced Electromagnetics, 2018)
In this paper, the effect of changing the structure of split ring resonator SRR from circular to elliptical shape is presented and tested. The theoretical analysis of circular SRR (CSRR) is tested and its results are compared with the simulated ones. Comparison between both configurations is introduced. The new elliptical SRR (ESRR) can be adapted to operate in multi range of frequencies. The effect of gap position in ESRR resonant is also examined. When both gaps are moved but still aligned, the resonant frequency still the same. But when single gap is moved only the resonant frequency the resonant frequency in changed to reach its maximum value when both gaps are in the same position. Frequency tunability can be offered by loading a single variable capacitor between ESRR metallic rings. The resonant frequency of the ESRR can be controlled by varying the capacitance of the varactor diode. Finite element method FEM is used to simulate the proposed structures using HFSS.